(untitled) (Ustozlar uchun, 2026)
This paper examines the theoretical and practical aspects of organizing freight transportation in various sectors of the economy, including industrial cargo. The study analyzes the processes of preparing goods for transportation, including the characteristics of wooden, metal, and vacuum packaging and their role in ensuring cargo safety. Issues related to proper loading and securing of cargo on transport vehicles, as well as monitoring and management of transportation processes using GPS tracking systems, are also discussed. Special attention is given to warehouse operations, cargo storage and handling processes, transport safety measures, and the specific characteristics of dangerous goods. In addition, the importance of insurance documents and the procedures for their preparation in freight transportation are highlighted. The research findings contribute to improving transportation efficiency, enhancing safety, and optimizing logistics processes.